Legal Dynamics of Age Limits for Presidential and Vice Presidential Candidates Based on Article 169 Letter Q of Law Number 7 of 2017 Concerning General Elections - Otni Magho, Alpian; Yusa, I Gede; Astariyani, Ni Luh Gede (West Science Interdisciplinary Studies, 2024)
Justice, non-discrimination, equality before the law are important values of the constitution. This study seeks to examine the constitutional rights of the younger generation that were cut by the framers of the law through the age requirement in the electoral law for presidential and vice presidential candidates. The research method used is a normative legal research method with qualitative methods. The age requirement no longer needs to be regulated in the Election Law because it is not in line and is not expressly regulated by the 1945 Constitution. If it is still regulated, the age requirement used must be 18 years, in accordance with the adult size applicable in Indonesia, as a consequence providing opportunities for the younger generation to participate in politics and government, and realize a more inclusive democracy. Factors influencing the setting of age requirements for presidential and vice presidential candidates are the history of national leadership, maintaining the status quo, and senior-junior practices. Therefore, Article 169 letter Q of the Election Law must be revised/deleted.